Tingkat Pengetahuan Generasi Millennial terhadap Faktor Resiko Diabetes Melitus Tipe 2: Millennials' Knowledge of Diabetes Risk Factors Mellitus Type 2 - Dikha Ayu Kurnia; Dewi Ayu Pratiwi (NERS Jurnal Keperawatan, 2021)
Today trend of fast food that contain lots of sweeteners and fats causes a change in food patterns and an unbalanced diet in the millennial generation. Consumption of excessive amounts of sweeteners and fatty food can cause obesity and insulin resistance which have implications on the occurrence of type 2 diabetes mellitus. Adequate knowledge related to this should be owned by the millennial generation so that they can minimize the risk and impact of the disease. However, there has been no research on millennial knowledge about the consumption sweeteners and fatty food. This study aims to describe the level of sweetener and fatty food knowledge in the millennial generation. This research method is analytical descriptive with cross sectional approach in millennial generation as many as 109 respondents. Research shows that 70.6% (n = 109) have sufficient knowledge. This research shows that the majority of respondents have sufficient knowledge of sweeteners and fatty foods so further education is needed.